2018
DOI: 10.1590/1984-70332018v18n3a39
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters and selection of macaw palm (Acrocomia aculeata) accessions: an alternative crop for biofuels

Abstract: This study aimed to estimate the parameters related to the genetic control of the physical characteristics of the fruits, oil content, and oil yield, and to proceed with the selection of macaw palm accessions. Forty-four macaw palm accessions of the active germplasm collection of the Federal University of Viçosa were collected for the evaluation of epicarp dry matter, pulp dry matter, endocarp dry matter, kernel dry matter, oil content, and oil yield. Narrow-sense individual heritability estimates were conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Domiciano et al (2015) point out that, assuming photosynthesis does not contribute significantly to the differentiation of A. aculeata progenies, incremental productivity gains depend on morphological rather than physiological improvements. Genetic parameters of specific traits of A. aculeata such as epicarp, pulp, endocarp, and kernel dry matter, as well as oil content and oil yield per plant indicate considerable genetic control (Costa et al 2018b). This was observed for oil yield in particular, the individual genetic variation of which suggests a high potential for selection and genetic gain (Costa et al 2018b).…”
Section: Morphological Traits Results Of Integral Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Domiciano et al (2015) point out that, assuming photosynthesis does not contribute significantly to the differentiation of A. aculeata progenies, incremental productivity gains depend on morphological rather than physiological improvements. Genetic parameters of specific traits of A. aculeata such as epicarp, pulp, endocarp, and kernel dry matter, as well as oil content and oil yield per plant indicate considerable genetic control (Costa et al 2018b). This was observed for oil yield in particular, the individual genetic variation of which suggests a high potential for selection and genetic gain (Costa et al 2018b).…”
Section: Morphological Traits Results Of Integral Analysesmentioning
confidence: 99%
“…Mesocarp oil content exhibits a strong positive correlation with total fruit oil, but a negative correlation with the mesocarp's proportion of the whole fruit (Ciconini et al 2013;da Conceição et al 2015). Costa et al (2018b) observed a low correlation between oil content and oil yield per plant, which indicates that the latter depends more on the number of fruits per plant than on oil content of the individual fruits. Further information is needed on selection criteria such as fruit yield, oil concentrations, and corresponding correlations to assist the breeding of commercial varieties of acrocomia.…”
Section: Biometric Characteristics Of Oilsmentioning
confidence: 89%
“…A selective pressure of 11.72% was adopted, for a total of 30 genotypes; the direct gains for the studied traits were calculated and, subsequently, the selection index was obtained from the sum of ranks (ranks) of Mulamba and Mock (1978), based on genotypic values. This index has proven efficiency in diverse crops, such as potato (Terres et al 2015), alfalfa (Vasconcelos et al 2010), popcorn (Vieira et al 2017), macaúba palm (Costa et al 2018), yellow passion fruit (Krause et al 2012), and coffee (Carias et al 2016). It has proven to be reliable and has provided balanced cultivars.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it is emphasized that several authors, such as Krycki et al (2016), Costa et al (2018), Fachinetto et al (2018), Tolomeotti et al (2018) and Silva et al (2018), have carried out studies involving native species of economic importance, such as the present study.…”
Section: Meiotic Index and Pollen Viabilitymentioning
confidence: 96%